Resilient Scheduling of Smart Buildings under False Data Injection Attack - Sethi, Basant Kumar (IIT(BHU) Varanasi, 2022)
Abstract is available in the content.
Keywords: Resilient Scheduling; of Smart Buildings; under False; Data Injection Attack